تأثير أنماط القيادة الادارية في مستوى تحفيز العاملين - بلقاسم, بن ناجي; محمد الامين, احميمة; سامية, بوطيب (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى معرفة أثر أنماط القيادة الإدارية في مستوى تحفيز العاملين بمؤسسة مجمع اتصالات الجزائر بالوادي، حيث اعتمدنا على المنهج الوصفي التحليلي في جمع المعطيات و البيانات المتعلقة بموضوع الدراسة، ولتحقيق هذا الهدف استخدمنا الاستبيان كأداة للدراسة، و تم توزيع هذا الأخير داخل فروع المؤسسة في ( حساني عبد الكريم، حاسي خليفة، البياضة، و الفرع الواقع في حي 17 أكتوبر ) بعينة قدرها 40 عينة و تم استرجاع 35 منها، و بالاعتماد على برنامج SPSS من خلال استخدام بعض الأساليب الإحصائية المناسبة لفرضيات الدراسة و تساؤلاتها . و في الأخير أظهرت الدراسة أن أنماط القيادة الإدارية لها تأثير في مستوى تحفيز العاملين بالمؤسسة محل الدراسة " "This study aims to find out the impact of administrative leadership styles on the motivation level of employees at the Algeria Telecom Group Corporation in El-Wadi، where we relied on the descriptive analytical approach in collecting data and data related to the subject of the study، and to achieve this goal we used the questionnaire as a tool for the study، and the latter was distributed within the branches The institution in (Hassani Abdel Karim، Hassi Khalifa، Bayada، and the branch located in the 17th of October neighborhood) with a sample of 40 samples and 35 of them were retrieved، and based on the SPSS program through the use of some statistical methods appropriate to the hypotheses and questions of the study. Finally، the study showed that administrative leadership styles have an impact on the level of motivation of employees in the institution under study. "
Keywords: أنماط، القيادة الإدارية، مستوى تحفيز، العاملين، مجمع اتصالات الجزائر بالوادي .; styles، administrative leadership، level of motivation، employees، Algeria Telecom Complex in El-Wadi